Maternal cardiac function at 35–37 weeks' gestation: relationship with birth weight. (January 2017) - Guy, G. P.; Ling, H. Z.; Machuca, M.; Poon, L. C.; Nicolaides, K. H.
ABSTRACT: Objective: To evaluate the relationship between maternal cardiovascular parameters and neonatal birth weight and examine the potential value of these parameters in improving the prediction of small‐for‐gestational‐age (SGA) and large‐for‐gestational‐age (LGA) neonates provided by maternal characteristics and medical history. Methods: In 2835 singleton pregnancies maternal characteristics and medical history were recorded and maternal cardiovascular parameters were measured. The observed measurements of cardiovascular parameters were expressed as multiples of the normal median (MoM) values after adjustment for those characteristics found to provide a substantial contribution to their measurement. Regression analysis was used to determine the significance of association between the normalized values of the cardiovascular parameters with birth‐weight Z ‐score. Multivariable logistic regression analysis was then used to determine if the maternal factors, fetal biometry and maternal cardiovascular parameters had a significant contribution to predicting SGA and LGA neonates. The performance of screening was determined by the area under receiver–operating characteristics curves (AUC). Results: In the study population there were significant positive associations between maternal cardiac output and heart rate with neonatal birth‐weight Z ‐score, and significant negative associations between total peripheral resistance and mean arterial pressure (MAP) with neonatal birth‐weight Z ‐score. In pregnancies delivering SGA neonates ( n = 249 (8.8%)), cardiac output and heart rate were lower and total peripheral resistance and MAP were higher, whereas in pregnancies delivering LGA neonates ( n = 292 (10.3%)) cardiac output and heart rate were higher and total peripheral resistance and MAP were lower. The performance of screening for delivery of SGA neonates achieved by maternal characteristics and fetal biometry was not improved by the measurement of maternal cardiovascular parameters. There was a small but significant improvement in the performance of screening for delivery of LGA neonates by maternal factors and fetal biometry with the addition of maternal heart rate (comparison of AUC, P = 0.0095). Conclusions: There are significant associations between maternal cardiac output, heart rate, total peripheral resistance and MAP and neonatal birth‐weight Z ‐score; such findings reflect the close relationship between maternal cardiac function and fetal demands. However, assessment of these parameters at 35–37 weeks' gestation is unlikely to improve substantially the performance of screening for SGA or LGA neonates provided by a combination of maternal factors and fetal biometry. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.